Preaching Training as Institutional Branding: Strategic Adaptation Without Losing Core Islamic Identity in a Demographically Transitioning Boarding School - Shalihin Shalihin; BB Wiyono; Ach Rasyad (FALASIFA : Jurnal Studi Keislaman, 2026)
This phenomenological study examines how a systematic five-minute preaching training program (dakwah) functions as institutional branding in an Islamic boarding school navigating demographic transition from religious homogeneity to cultural diversity. Central to this inquiry is the tension of strategic adaptation without losing core Islamic identity how the institution responds to urbanization-driven diversification while preserving its authentic religious mission. Using Interpretative Phenomenological Analysis across four existential dimensions (lived body, lived time, lived space, lived relationship), twenty-four participants were engaged including institutional leaders, current students, alumni, and community members. Contrasting perspectives among three key informants illuminate this tension vividly: institutional leaders assert that traditional preaching methods must be preserved as non-negotiable identity anchors; alumni actively engaged in dakwah describe how the program formed their religious leadership identity in ways no classroom instruction could; while community members receiving student preaching testify that the broadcasts create daily lived connection between the institution and the surrounding diverse neighborhood. Findings reveal three dimensions: the program functions as culturally-responsive local content curriculum preserving Islamic scholarly tradition; systematic daily practice develops students' religious leadership and public communication competency through experiential learning; and the distinctive program serves as effective institutional branding recognized by diverse stakeholders as authentic religious leadership development. This study contributes to understanding how religious educational institutions navigate social change while maintaining cultural-religious authenticity through distinctive pedagogical innovation.